Left ventricular dimensions, systolic functions, and mass in term neonates with symmetric and asymmetric intrauterine growth restriction. (20th December 2013) - Cinar, Bahar; Sert, Ahmet; Gokmen, Zeynel; Aypar, Ebru; Aslan, Eyup; Odabas, Dursun
Abstract Background: Previous studies have demonstrated structural changes in the heart and cardiac dysfunction in foetuses with intrauterine growth restriction. There are no available data that evaluated left ventricular dimensions and mass in neonates with symmetric and asymmetric intrauterine growth restriction. Therefore, we aimed to evaluate left ventricular dimensions, systolic functions, and mass in neonates with symmetric and asymmetric intrauterine growth restriction. We also assessed associated maternal risk factors, and compared results with healthy appropriate for gestational age neonates. Methods: In all, 62 asymmetric intrauterine growth restriction neonates, 39 symmetric intrauterine growth restriction neonates, and 50 healthy appropriate for gestational age neonates were evaluated by transthoracic echocardiography. Results: The asymmetric intrauterine growth restriction group had significantly lower left ventricular end-systolic and end-diastolic diameters and posterior wall diameter in systole and diastole than the control group. The symmetric intrauterine growth restriction group had significantly lower left ventricular end-diastolic diameter than the control group. All left ventricular dimensions were lower in the asymmetric intrauterine growth restriction neonates compared with symmetric intrauterine growth restriction neonates (p>0.05), but not statistically significant except left ventricular posterior wall diameter in diastole (3.08±0.83 mm versus 3.54 ±0.72 mm) (p<0.05). Both symmetric and asymmetric intrauterine growth restriction groups had significantly lower relative posterior wall thickness (0.54±0.19 versus 0.48±0.13 versus 0.8±0.12), left ventricular mass (9.8±4.3 g versus 8.9±3.4 g versus 22.2±5.7 g), and left ventricular mass index (63.6±29.1 g/m2 versus 54.5±24.4 g/m2 versus 109±28.8 g/m2) when compared with the control group. Conclusions: Our study has demonstrated that although neonates with both symmetric and asymmetric intrauterine growth restriction had lower left ventricular dimensions, relative posterior wall thickness, left ventricular mass, and mass index when compared with appropriate for gestational age neonates, left ventricular systolic functions were found to be preserved. In our study, low socio-economic level, short maternal stature, and low maternal weight were found to be risk factors to develop intrauterine growth restriction. To our knowledge, our study is the first to evaluate left ventricular dimensions, wall thicknesses, mass, and systolic functions in neonates with intrauterine growth restriction and compare results with respect to asymmetric or symmetric subgroups.